Cartas, favores, família e poder : a trajetória e o epistolário de um comerciante português na Província do Rio Grande do Sul - Carvalho, Djiovan Vinícius (2020)
The historiographic renewal that has occurred in Brazil since the 1980s, supported by the insertion of new theoretical and methodological possibilities and the use of diversified historical sources, alongside the “reinsertion” of individuals within history, has allowed the expansion of biographical studies, frequently from their personal documents. Hence, this research intends to accompany the “making of oneself” of a specific individual, following the set of actions performed by him, in order to understand his social insertion, relational practices and aspirations, from the correspondence preserved in his epistolary. This is the Portuguese merchant Antonio da Silva Vasconcellos, who immigrated in 1851, initially settling in Rio de Janeiro. Ten years later, Vasconcellos migrated to the Province of São Pedro do Rio Grande do Sul, residing and establishing social bonds, especially in the cities of São Gabriel and São Vicente. Thus, the objective was to comprehend the social practices, of economic, political and social order, in the interior of Rio Grande do Sul, based on the construction of networks and bonds and the ascension or maintenance of social positions, through the survey, reading and analysis of its personal epistolary, examining the missives qualitatively and quantitatively, together with the collation of other documentary sources. The study sought to reconstitute Vasconcellos’ life history and, consequently, part of the social network in which he was inserted. Therefore, it was confirmed that personal letters are considered privileged sources, as they gather information that allows the understanding of certain historical contexts, through the reading of the exchange of favors, pacts and relationships, both professional and affective, among several individuals, with epistolary writing being an eminently relational practice. Additionally, it has been concluded that the Portuguese merchant Antonio da Silva Vasconcellos has, throughout his life, managed strategies to ascend socially, economically and politically, using resources and contacts to his benefit and distinguishing himself from his fellow contemporaries by having had part of his daily life preserved in his correspondence.